Current Driver Design for Electromagnetic Coil Using Adaptive Active Disturbance Rejection Control - Hongtao Zhu; Xiaoting Rui; Fufeng Yang; Wei Zhu (Shock and Vibration)
An adaptive active disturbance rejection controller is used in the current driver design of the electromagnetic coil. Extended state observer of the 1st-order system is adopted for disturbance observation of ADRC. The supervised recursive least squares method is proposed for real-time parameters estimation, in which the excitation signal variance is used to trigger the parameter estimator. The experimental results demonstrate that ADRC combined with real-time parameter estimation simplifies the parameter tuning and improves the parameter adaptive ability.